Wildlife diversity near natural saltlicks in the Ulu Muda forest reserve - Zalina Bashir Ali (WWF Report Malaysia 2014, 2014)
This report is based on the interest of conserving Ulu Muda's saltlicks as important resources for wildlife and how WWF-Malaysia suggests the implementation of the management recommendations.